Analisis Implementasi Regulasi Penetapan Status Perlindungan Terbatas Ikan Terubuk (Tenualosa ilisha) - Siregar, Awaluddin M; Kuswardani, Retna Astuti; Hasibuan, Syahbuddin (Universitas Medan Area, 2020)
This study aims to determine the form of implementation, find out from the implementation and find out the obstacles and constraints in implementing the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number: 43 / KEPMEN-KP / 2016 on the availability of terubuk fish resources and fishermen income in Labuhanbatu Regency. In scientific research that uses qualitative approaches with interpretative normative paradigms, existing theories used in research are constructed as imperfect buildings, this research is descriptive in nature. It can be illustrated that the Implementation of the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number: 43 / KEPMEN-KP / 2016 concerning Limited Protection of Terubuk Fish (Tenualosa ilisha) has been carried out in the form of socialization, sea patrol and monitoring activities carried out by the Government, the Indonesian National Army, Police and community watch groups. The effectiveness of the implementation of the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia on the availability of fish resources legally and seen from the catches of fishermen has increased and is quite effective, but not yet significant because the enforcement of sanctions for violations has not yet materialized and the obstacles and constraints of the implementation of the Decree are the implementation of regulations which is not widely socialized, is not accompanied by the assistance of facilities and infrastructure for fishermen is very minimal and not in accordance with the socio-cultural community that is more bound to local wisdom